Covalent post-assembly modification in metallosupramolecular chemistry. (16th November 2017) - Roberts, Derrick A.; Pilgrim, Ben S.; Nitschke, Jonathan R.
Abstract : This review examines the growing variety of covalent reactions used to achieve the post-assembly modification of self-assembled metallosupramolecular complexes. Abstract : A growing variety of covalent reactions have been employed to achieve the post-assembly modification (PAM) of self-assembled metallosupramolecular complexes. Covalent PAM enables the late-stage derivatisation of pre-assembled parent complexes in a modular fashion, thus expanding the chemical space available for supramolecular synthesis. The oldest and most widespread implementation of covalent PAM is in metal-preorganised covalent synthesis. Recent work, however, has broadened the scope of covalent PAM to include: protocols for efficiently grafting new functionalities onto supramolecular architectures, reactions that permanently 'lock-down' metastable complexes, and covalent bond-forming stimuli that trigger controlled structural transformations between distinct supramolecular species. This review highlights key examples of each of these distinct kinds of covalent PAM in metallosupramolecular chemistry, before providing a perspective upon future challenges and opportunities.